2013
DOI: 10.5051/jpis.2013.43.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microthreads on removal torque and bone-to-implant contact: an experimental study in miniature pigs

Abstract: PurposeThe objective of this study was to evaluate the effect of microthreads on removal torque and bone-to-implant contact (BIC).MethodsTwelve miniature pigs for each experiment, a total of 24 animals, were used. In the removal torque analysis, each animal received 2 types of implants in each tibia, which were treated with sandblasting and acid etching but with or without microthreads at the marginal portion. The animals were sacrificed after 4, 8, or 12 weeks of healing. Each subgroup consisted of 4 animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…The measured BIC of implants inserted according to DP1 and DP2 was comparable for all of the implant types after both 1 m and 3 m of healing for each drilling protocol and ranged from 75-96% after 3 m without significant differences among the implant types or between the drilling protocols. The reported BIC is in agreement with that in a study conducted by Kwon, who reported that the BIC of implants inserted in minipigs ranged from 71-82% after 1 m of healing [32].…”
Section: Discussionsupporting
confidence: 91%
“…The measured BIC of implants inserted according to DP1 and DP2 was comparable for all of the implant types after both 1 m and 3 m of healing for each drilling protocol and ranged from 75-96% after 3 m without significant differences among the implant types or between the drilling protocols. The reported BIC is in agreement with that in a study conducted by Kwon, who reported that the BIC of implants inserted in minipigs ranged from 71-82% after 1 m of healing [32].…”
Section: Discussionsupporting
confidence: 91%
“…This makes it possible to distribute the stress more evenly, increasing MI stability. 19,20 Kwon et al 19 did not find significant mechanical and histological differences, in terms of removal torque and bone/implant contact, when comparing implants with and without microthreads. However, Chang et al, 20 using mechanical and finite element analysis, concluded that modification of MI design can affect mechanical properties, improving primary stability.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…The case number was planned to be equal if not higher than in current similar studies comparing titanium implant surfaces in vivo. [35][36][37] For evaluation, a total of 84 implants (uncoated, n = 36; streptavidin-biotin, n = 24; and streptavidin-biotin-fibronectin, n = 24) were available. Half of them were analyzed after 3, the other half after 6 weeks.…”
Section: Discussionmentioning
confidence: 99%